Associating great ancient philosophers to current mathematical practice - Hassan, Aminuddin; Zainal Abiddin, Norhasni; Mohd Ayub, Ahmad Fauzi (Elsevier, 2010)
Teaching and learning mathematics require a set of appreciation, methodology, approaches and relationship. The process of understanding and mastering the skill involves few stages, starting from pre-school education (i.e. before the age of seven), primary education, secondary education to tertiary education, as well as further improves through job requirements or daily applications. Mathematical teaching is beneficial for the usage of each stage respectively. However, lack of appreciation or effort in mastering it will lead to negative implications. The subject of Mathematics inclines towards the application of deductive reasoning. Furthermore, everyone will continue to apply the knowledge of Mathematics throughout their life, regardless of age, situation, condition and awareness. Mathematical application is useful, not only to the adolescents and adults, but also to the children. The philosophy of mathematic, in guiding any mathematical activities and practices, has actually started way back in the ancient times. It comes from the mind of the philosophers based on their own context. During that period, people relied on whatever advice and instruction from the authorities, who were mostly philosophers. Therefore, we can refer to what they had argued on mathematical aspects, which will provide many benefits, which will cause strong impact to the modern mathematical applications. The discoveries of mathematical principles among ancient philosophers or mathematic philosophers brings a lot of impact to today's application and practices in dealing with sophisticated living system and society. In brief, it is indeed important to analyse the thoughts of ancient philosophers in relation to mathematics, which started many years back before century. Concepts and theories of mathematics that were explored, introduced and proposed during that time show that mathematical knowledge is a universal knowledge that will be used forever. The knowledge has always been available since the creation of human. Thus, it is depends solely on when and who will introduce or explore any part or principle of this knowledge for specific or future purposes.